Iron Physiological Requirements of Pregnant Women Assessed by the Stable Isotope Tracer Technique (P24-062-19) - Yang, Lichen; Lu, Jiaxi; Li, Min; Cai, Jie; Ma, Yuxia; Yang, XIaoguang (Current developments in nutrition, 2019)
Iron physiological requirement, the core index to formulate the dietary reference intakes (DRIs), is of great importance for the health of pregnant women and fetus and can help the mother to accurately plan iron supplement. While the direct measurement data of iron physiological requirements in pregnancy is still lacking worldwide, the objective of this study is to assess this value in Chinese pregnant women by stable isotope tracer technique. 11 women of reproductive age who had been pregnant during the study from Hebei province in 2015 were included in the final analysis. Subjects were participated in a two-week metabolic test with oral intake of 50 mg 58Fe and followed up to about 2 years. The abundance of 58Fe and the total iron concentration was detected by MC-ICP-MS and AAS. The iron physiological requirements in pregnancy were calculated by the formula. The average iron physiological requirement of 11 subjects in the whole pregnancy was 3054.12 μg/d in total and 43.99 μg/(kg.d) after weight adjusted. The iron physiological requirement in the first, second and third trimester was 2039.07 μg/d, 3258.90 μg/d and 4134.47 μg/d, respectively. The iron physiological requirement adjusted by weight in the first, second and third trimester was 32.28 μg/(kg.d), 46.90 μg/(kg.d) and 55.74 μg/(kg.d), respectively. Comparing the results of each pregnancy period, there was no significant difference (P > 0.05). The pregnant women need more than 2 times iron over that of the non-pregnant. The iron physiological requirements in different trimester showed no significant difference, while there was an increasing trend of requirements went with the pregnancy progress. National Natural Science Foundation of China (https://isisn.nsfc.gov.cn/egrantindex/funcindex/prjsearch-list, grant no.:81,330,066)